Review of Regulatory Framework Governing Digital Tourism Information Center Program Based on Regulatory Impact Assessment - Tiara Azani; Laga Sugiarto (Law Research Review Quarterly, 2025)
This study evaluates the Tourism Information Center (TIC) Digital Nusantara’s regulatory framework regarding industrial efficiency. The primary issue is the fragmented, non-binding nature of current circular letters, leading to inconsistent implementation and budgetary waste. Using normative legal research and the Regulation Impact Assessment (RIA) framework, findings show that existing executive rule-making provides flexibility but fails to ensure national data integration. Aligned with Presidential Instruction No. 1/2025 on budget efficiency, this study concludes that a non-regulatory approach—revising technical guidelines and strengthening private-sector partnerships is more effective than creating rigid new regulations. Therefore, the government must prioritize data interoperability standards and formalize digital platform cooperation to ensure a cost-effective, integrated tourism ecosystem.